Perioperative outcomes following robot-assisted partial nephrectomy for complex renal masses: A Vattikuti Collective Quality Initiative database study - Sharma, Gopal; Shah, Milap; Ahluwalia, Puneet; Dasgupta, Prokar; Challacombe, Benjamin J.; Bhandari, Mahendra; Ahlawat, Rajesh; Rawal, Sudhir; Buffi, Nicolo M.; Sivaraman, Ananthakrishnan; Porter, James R.; Rogers, Craig; et al. (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2022)
Introduction: Outcomes of robot-assisted partial nephrectomy (RAPN) depend on tumor complexity, surgeon experience and patient profile among other variables. We aimed to study the perioperative outcomes of RAPN for patients with complex renal masses using the Vattikuti Collective Quality Initiative (VCQI) database that allowed evaluation of multinational data. Methods: From the VCQI, we extracted data for all the patients who underwent RAPN with preoperative aspects and dimensions used for an anatomical (PADUA) score of >= 10. Multivariate logistic regression was conducted to ascertain predictors of trifecta (absence of complications, negative surgical margins, and warm ischemia times {[}WIT] <25 min or zero ischemia) outcomes. Results: Of 3,801 patients, 514 with PADUA scores >= 10 were included. The median operative time, WIT, and blood loss were 173 (range 45-546) min, 21 (range 0-55) min, and 150 (range 50-3500) ml, respectively. Intraoperative complications and blood transfusions were reported in 2.1\% and 6\%, respectively. In 8.8\% of the patients, postoperative complications were noted, and surgical margins were positive in 10.3\% of the patients. Trifecta could be achieved in 60.7\% of patients. Clinical tumor size, duration of surgery, WIT, and complication rates were significantly higher in the group with a high (12 or 13) PADUA score while the trifecta was significantly lower in this group (48.4\%). On multivariate analysis, surgical approach (retroperitoneal vs. transperitoneal) and high PADUA score (12/13) were identified as predictors of the trifecta outcomes. Conclusion: RAPN may be a reasonable surgical option for patients with complex renal masses with acceptable perioperative outcomes.